Blockades of nerves of lower extremity in pediatrics: practical aspects (Pain medicine, 2017)
This article cover the use of blockades of nerves of lower extremity in pediatric practice. It is known that regional anesthesia in pediatric practice is a rapidly developing area of domestic anesthesiology. The current concept of balanced anesthesia considers regional blockades not only as an isolated method and an alternative to general anesthesia, but as an important and integral component of the latter one, allowing to significantly reduce the concentration and dosing of inhalation and intravenous anesthetics, narcotic analgesics. The regional block allows to obtain an exceptionally effective postoperative analgesia without side effects inherent in many drugs used traditionally. In operations on lower extremities, children have central epidural block at the lumbar and caudal level, as well as blockade of nerves of lumbar and sacral plexuses, depending on the surgical intervention zone, the duration and traumatism of operation, and some of the methods of regional anesthesia are examined and presented in the article.
Keywords: regional anesthesia; analgesia; pain; lower extremity; nerves